Strength training considerations for a dwarf track and field thrower - Lane, C. T. (Journal of Australian Strength and Conditioning, 2017)
The purpose of this article was to detail observations and considerations of implementing a strength and conditioning program for a female dwarf athlete. Observations were made of an implemented strength-training program for one female dwarf track and field thrower (age: 21years, height: 128cm; weight: 62kg) across a competitive season. Results demonstrated physical improvements in bench press performance (6%), isometric mid-thigh pull (25%), bench throw peak power (6%), peak velocity (6%) at 25kg (~30% of 1RM bench press), bodyweight countermovement jump peak power (13%), and bodyweight (16%). Throwing performance at major competition one was 7.57 meters and 24.59 meters and at major competition two was 8.14 meters and 23.27 meters for shot put and discus throw respectively. Due to dwarf morphology, modifications requiring consideration include; equipment and exercise selection (due to difficulties handling equipment), acute and chronic adjustments to daily training environment following acute athlete presentation, and effective use of training time. Observations of this athlete indicate that dwarf athletes have the ability to participate and improve physical capacities of muscular strength and power by making adjustments to a typical strength and conditioning program. These adjustments include considerations to exercise selection, acute and chronic training schedule modifications, and specialised equipment use.